Branched glycerol dialkyl glycerol tetraethers distributions from seven loess-paleosol sequences across the Chinese Loess Plateau over the past 40,000 years - Guo, Jingjing; Fuchs, Louise; Ziegler, Martin; Yin, Qiuzhen; Wu, Zhipeng; Hao, Lu; Sun, Youbin; Peterse, Francien (PANGAEA, 2026)
In this dataset, the fractional abundance of branched glycerol dialkyl glycerol tetraethers (brGDGTs) and the temperature records based on brGDGT proxy over the past ~40,000 years from seven loess-paleosol sequences on the CLP are included. The brGDGT records for Guojiapan and Bailu are extracted in this study, the brGDGT records for Mangshan has been published based on old analytical method (Peterse et al., 2014), we re-run these samples using the new analytical method for this study, the brGDGT records for Yuanbao (Guo et al., 2024, Climate of the Past), Xifeng (Lu et al., 2019, Nat. Commun.), Lingtai (Fuchs et al., 2022, QSR), and Weinan (Tang et al., 2017, EPSL) are complied from previous publications.